Topics of Nicotine-Related Discussions on Twitter: Infoveillance Study - Allem, Jon-Patrick; Dormanesh, Allison; Majmundar, Anuja; Unger, Jennifer B; Kirkpatrick, Matthew G; Choube, Akshat; Aithal, Aneesh; Ferrara, Emilio; Boley Cruz, Tess (JMIR Publications, 2021)
BackgroundCultural trends in the United States, the nicotine consumer marketplace, and tobacco policies are changing. ObjectiveThe goal of this study was to identify and describe nicotine-related topics of conversation authored by the public and social bots on Twitter, including any misinformation or misconceptions that health education campaigns could potentially correct. MethodsTwitter posts containing the term "nicotine" were obtained from September 30, 2018 to October 1, 2019. Methods were used to distinguish between posts from social bots and nonbots. Text classifiers were used to identify topics in posts (n=300,360). ResultsPrevalent topics of posts included vaping, smoking, addiction, withdrawal, nicotine health risks, and quit nicotine, with mentions of going "cold turkey" and needing help in quitting. Cessation was a common topic, with mentions of quitting and stopping smoking. Social bots discussed unsubstantiated health claims including how hypnotherapy, acupuncture, magnets worn on the ears, and time spent in the sauna can help in smoking cessation. ConclusionsHealth education efforts are needed to correct unsubstantiated health claims on Twitter and ultimately direct individuals who want to quit smoking to evidence-based cessation strategies. Future interventions could be designed to follow these topics of discussions on Twitter and engage with members of the public about evidence-based cessation methods in near real time when people are contemplating cessation.